Tannhauser and the tournament of song at wartburg romatic opera in three acts Novello's original octavo edition - WAGNER, Richard (Novello Ewer and co)
Overturenscene I The hill of venusnscene II venus and tannhausernscene III tannhauser, ayoung shepherd, adn the elder pilgrimsnscene IV tannhauser, the landgrave and minstel knights